2018
DOI: 10.1002/jsde.12195
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions of Branched Fatty‐Acid Calcium Salt/Water Systems

Abstract: Calcium (Ca) salts of fatty acids are powder materials, which exhibit lubricant, hydrophobic, and bactericidal properties. These physical and biological properties depend on the chemical structure of the alkyl chain of the fatty acids. In this study, the phase behavior of iso‐stearic acid Ca salt/water binary systems was studied, and the effect of the branched structure in the alkyl chain was analyzed. Herein, calcium chloride is added to the iso‐stearic acid aqueous solution. The state of the binary systems c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…It is known that, in the presence of water, salts of fatty acids can form liquid crystalline structures, as has been reported for calcium salts of stearic acid and water. 57 The structural state of a phase can be addressed by computational methods and/or diffraction methods, but ssNMR methods may also provide structural and crystallographic information on samples as varied as reasonably large proteins and pharmaceutical compounds. 58 Low solubilities of the metal carboxylates make it extremely difficult, if not impossible, to grow single crystals of these compounds sufficient to obtain X-ray diffraction structures.…”
Section: Structure Of Lead Soaps By Ssnmr Spectroscopymentioning
confidence: 99%
“…It is known that, in the presence of water, salts of fatty acids can form liquid crystalline structures, as has been reported for calcium salts of stearic acid and water. 57 The structural state of a phase can be addressed by computational methods and/or diffraction methods, but ssNMR methods may also provide structural and crystallographic information on samples as varied as reasonably large proteins and pharmaceutical compounds. 58 Low solubilities of the metal carboxylates make it extremely difficult, if not impossible, to grow single crystals of these compounds sufficient to obtain X-ray diffraction structures.…”
Section: Structure Of Lead Soaps By Ssnmr Spectroscopymentioning
confidence: 99%
“…The excellent lubricity results from (i) the cleavage of lamellar layers of the powdered aggregates, (ii) the disintegration of the aggregates, and (iii) the low surface energy of the calcium salts, leading to increased hydrophobicity of solid surfaces 6−9) . The authors also demonstrated the phase transitions of the calcium salt of a branched fatty acid (2,2,4,8,10,10-hexamethylundecane-5-carboxylic acid, generally called iso-stearic acid ) with water 10) . The key finding of this study was that the calcium salt yields a liquid crystal phase at low Ca 2+ mole ratios, despite the calcium salt of octadecanoic acid (n-stearic acid) exhibiting a gel phase under the corresponding conditions.…”
Section: Introductionmentioning
confidence: 98%